Framework and components for effective discharge planning system: a delphi methodology - Yam Carrie HK; Wong Eliza LY; Cheung Annie WL; Chan Frank WK; Wong Fiona YY; Yeoh Eng-kiong (BMC, 2012)
Abstract Background To reduce avoidable hospital readmissions, effective discharge planning and appropriate post discharge support care are key requirements. This study is a 3-staged process to develop, pretest and pilot a framework for an effective discharge planning system in Hong Kong. This paper reports on the methodology of Delphi approach and findings of the second stage on pre-testing the framework developed so as to validate and attest to its applicability and practicability in which consensus was sought on the key components of discharge planning. Methods Delphi methodology was adopted to engage a group of experienced healthcare professionals to rate and discuss the framework and components of an effective discharge planning. The framework was consisted 36 statements under 5 major themes: initial screening, discharge planning process, coordination of discharge, implementation of discharge, and post discharge follow-up. Each statement was rated independently based on 3 aspects including clarity, validity and applicability on a 5-point Likert-scale. Statement with 75% or above of participants scoring 4-5 on all 3 aspects would be included in the discharge planning framework. For those statements not reaching 75% of consensus in any one of the aspect, it would be revised or discarded following the group discussion, and be re-rated in another round. Results A total of 24 participants participated in the consensus-building process. In round one rating, consensus was achieved in 25 out of 36 statements. Among those 11 statements not reaching consensus, the major concern was related to the "applicability" of the statements. The participants expressed a lack of manpower, skills and time in particular during weekends and long holidays in carrying out assessment and care plans within 24 h after admission. There were also timeliness and availability issue in providing transportation and necessary equipment to the patients. To make the statements more applicable, the wordings of some of the statements were revised to provide greater flexibility. Due to the lack of a statement in clarifying the role of the members of the healthcare professional team, one additional statement on the role and responsibility of the multidisciplinary team members was added. The first theme on "initial screening" was further revised to "initial screening and assessment" to better reflect the first stage of discharge planning process. After two rounds of rating process, all the 36 statements and the newly added statement reached consensus Conclusions A structured, systematic and coordinated system of hospital discharge system is required to facilitate the discharge process to ensure a smooth patient transition from the hospital to the community and improve patient health outcome in both clinical and social aspect. The findings of this paper provide a reference framework helping policymakers and hospital managers to facilitate the development of a coherent and systematized discharge planning process. Adopting a Delphi approach also demonstrates the values of the method as a pre-test (before the clinical run) of the components and requirements of a discharge planning system taking into account of the local context and system constraints, which would lead to improvements to its applicability and practicability. To confirm the applicability and practicability of this consensus framework for discharge planning system, the third stage of process of development of the discharge planning framework is to apply and pilot the framework in a hospital setting to evaluate its feasibility, applicability and impact in hospital including satisfaction from both the perspectives of staff and patients.